Optimasi Pemodelan Hujan Limpasan dan Analisis Genangan Banjir untuk Evaluasi Dampak Infrastruktur DAS Rea - Amitaba, Ida Wayan; Pramudiya, Asrul; Ahyadi, Hendra; Ranesa, Lalu Sigar Canggih (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2025)
Flood disasters, with their increasingly common occurrence and shorter peak discharge times, have led to more significant runoff and elevated flood risks. Taliwang City, the economic center of West Sumbawa Regency, is particularly vulnerable to flooding, despite the presence of the natural reservoir, Lake Lebo Taliwang. The construction of the parallel Bintang Bano and Tiu Suntuk dam is expected to significantly reduce flood impacts. This study aims to analyze peak flood discharge and conduct flood inundation modeling to assess how reservoir routing from dam inflow and Lake Lebo Taliwang affects flood conditions in the Rea watershed. Flood discharge analysis was performed by converting rainfall data into flow hydrographs using HEC-HMS software, while flood inundation modeling was carried out using HEC-RAS (2D) software. The input for the HEC-RAS model included flood inflow from the Rea sub-watershed, differentiated by the 50-year return period (Q50) discharge, both before and after considering the effects of reservoir routing. The results showed a significant reduction in peak discharge for the Q50 return period post-dam construction, decreasing from 3,198.42 m³/s to 1,575.72 m³/s—a reduction of 50.73%. Additionally, the area affected by flooding shrank by a substantial 33.96%, from 4,016 hectares to 2,652 hectares, demonstrating the practical benefits of the dam construction. The depth of flooding along the riverbanks decreased from 1.14 meters to 0.63 meters, while it was reduced in Taliwang City from 0.42 meters to 0.08 meters.